Outcome of lung transplantation in non‐idiopathic pulmonary fibrosis interstitial lung disease. Issue 10 (6th August 2019) - Bode, Hannelore; Verleden, Stijn E.; Wuyts, Wim A.; Yserbyt, Jonas; Verleden, Geert M.; Vos, Robin
Abstract: Lung transplantation remains the only curative treatment option for selected patients with end‐stage interstitial lung disease (ILD). Candidate selection is impeded by patient heterogeneity, particularly in the subgroup of non‐idiopathic pulmonary fibrosis (non‐IPF) interstitial lung diseases. We performed a descriptive analysis of all non‐IPF ILD patients who underwent lung transplantation in our center between July 1991 and November 2016 (n = 129) and searched for pre‐transplant variables correlating with graft loss and chronic lung allograft dysfunction (CLAD). Our study cohort was characterized by a significantly affected medical condition, an extensive pre‐transplant corticosteroid use (73.8%), and a high prevalence of pulmonary hypertension (55.7%). Earlier year of transplantation ( P  = .004), higher bilirubin level ( P  < .0001), older recipient age ( P  = .04), and smaller recipient height ( P  = .02) were found to be associated with earlier graft loss in multivariate analysis. Moreover, pre‐transplant corticosteroid treatment tended to be related to earlier graft loss ( P  = .06), while pulmonary hypertension did not significantly correlate. None of the pre‐transplant variables were shown to be associated with CLAD development. Ongoing research is required to further explore this diverse patient population and the pre‐transplant variables determining their post‐transplant outcome.